STOCK ASSESSMENT OF COMMON CARP CYPRINUS CARPIO IN EUPHRATES RIVER, NEAR AL-MUSSAIB POWER STATION - MOHAMED, A. R. M .; ALRUDAINY, A. J.; ABBAS, L. M. (Iraqi Journal of Aquaculture, 2022)
The stock of common carp Cyprinus carpio in Euphrates river, near Al-Mussaib power station was studied from September 2002 to December 2003. A total of 766 specimens were collected, their total lengths ranged from 6.2 to 55.4cm and between 9-5500g in total weight. The catch rate was ranged between 8.4Kg/h in Summer to 30.2Kg/h in Spring. Length-weight relationship was W= 2.7 x 10-4 L 3.04. The lengths of fish were 23, 37, 48 and 54cm for the ages 1-4 years respectively. Growth and mortality parameters estimated were: Ld= 65cm, K= 0.26, Z= 1.02, M= 0.60 and F= 0.42. The exploitation rate (E) of carp was 0.41, lower than the optimum level. The values of Lc and Lm were 18cm and 27.1cm respectively and 55.3% of population was immature. A bimodal recruitment pattern of unequal strength was observed, the major contribution was 71.9% of the total recruits with a peak in May and the minor was contributed 28.1% with a peak in October.